2020
DOI: 10.1186/s12974-020-01991-2
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol mediates mechanical allodynia through modulating inflammatory response via the TREM2-autophagy axis in SNI rat model

Abstract: Background Neuropathic pain (NeuP) is a chronic and challenging clinical problem, with little effective treatment. Resveratrol has shown neuroprotection by inhibiting inflammatory response in NeuP. Recently, the triggering receptor expressed on myeloid cells 2 (TREM2) expressed by microglia was identified as a critical factor of inflammation in nervous system diseases. In this study, we explored whether resveratrol could ameliorate neuroinflammation and produce anti-mechanical allodynia effects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 45 publications
0
41
2
Order By: Relevance
“…TREM2 knockout alveolar macrophages displayed augmented bacterial phagocytosis in vitro and in vivo compared to WT alveolar macrophages [ 34 ]. On the other hand, researchers have found that TREM2 suppresses inflammation by attenuating microglial activation [ 32 ], suppressing PI3K/NFκB signaling [ 35 , 36 ], downregulating TLR signaling [ 37 , 38 , 39 ], and modulating the TREM2-autophagy axis [ 39 ]. TREM2 also modifies the microglial phenotype and provides neuroprotection in P301S tau transgenic mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…TREM2 knockout alveolar macrophages displayed augmented bacterial phagocytosis in vitro and in vivo compared to WT alveolar macrophages [ 34 ]. On the other hand, researchers have found that TREM2 suppresses inflammation by attenuating microglial activation [ 32 ], suppressing PI3K/NFκB signaling [ 35 , 36 ], downregulating TLR signaling [ 37 , 38 , 39 ], and modulating the TREM2-autophagy axis [ 39 ]. TREM2 also modifies the microglial phenotype and provides neuroprotection in P301S tau transgenic mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no direct evidence that inhibition of apoptotic activities in the injured neurons can attenuate pain behavior. In contrast to apoptosis, many studies with different animal models have shown changed autophagic activities in the injured nerve [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ], spinal cord [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and even brain [ 43 ] after nerve injury. These studies also showed that upregulated autophagic activities can directly alleviate neuropathic pain [ 24 , 26 , 27 , 32 , 33 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“… [ 92 ] Neuropathic pain Sprague Dawley rats Rats constructed for neuropathic pain were treated with RSV by intraperitoneal injection (300 ug/day) RSV reduced neuroinflammation and neuropathic pain in rats by inhibiting autophagy via downregulating the TREM2 signaling pathway. [ 93 ] …”
Section: Discussionmentioning
confidence: 99%
“…All these functions of RSV aid repress the instigation and development of inflammation. Moreover, studies have shown that RSV could improve autophagy [ 93 ] when inflammation occurs.…”
Section: Introductionmentioning
confidence: 99%